Administração de materiais aplicada na policlínica odontológica da UEA - Reis, Jorge Luiz Xavier (2021)
The present work refers to the analysis of the UEA Dental Polyclinic, aiming only to focus on its procedures that are pertinent to the administration of materials, in such a way that, at the end of this analysis, it is possible to compare its competences against the administrative ideals of the authors cited in this work. The research methodology is characterized as descriptive in terms of its objectives and qualitative in terms of the analysis of its problems. The main data collection technique was the application of a checklist accompanied by individual interviews with all the company's professionals who deal with storage. The main purpose of this work was to identify the biggest problems facing the unit's materials administration and, through theoretical foundation, recommend actions to solve these problems. The results show that the greatest difficulty in managing the organization's materials is the lack of space and, to try to solve this problem, the application of input organization methods (Curve ABC) and methods of streamlining the flow of materials (Lung and Picking).